The Effect of Corporate Social Responsibility on Firm Value with Tax Avoidance and Sustainable Financial Performance as Mediators - Graciella Tanaya; Hatane Semuel; Devie Devie (Petra International Journal of Business Studies, 2023)
Research confirms the influence of corporate social responsibility on firm value through tax avoidance and sustainable financial performance. Corporate social responsibility is measured based on the ESG disclosure score. In contrast, firm value is measured using Tobin's Q. Tax avoidance is measured using the effective tax rate, and sustainable financial performance is measured using return on assets. The samples analyzed in this research were 93 public companies listed on the IDX from all sectors. This research uses a purposive sampling method to produce reports on 93 companies in 5 years of company financial reports in 2017-2021. Data analysis used the Partial Least Square SEM technique. The analysis results show that corporate social responsibility has a significant direct effect on firm value, while the mediating role of tax avoidance and sustainable financial performance is not proven. In this research, it can be seen that corporate social responsibility (CSR) has a direct influence on firm value. This shows that stakeholders rely on CSR as a positive image of the company, as in several previous research results, it can describe the value of the company, which has an impact on investors' decisions to invest but indirectly does not influence tax avoidance and sustainable financial performance. The results of this research can provide an additional understanding of the previous theoretical concept that CSR can directly influence firm value. The strategic implications, of course, depend on company decision-makers in communicating CSR activities in their reports when they want investors' attention to the firm value.